The benefits for health care staff of involvement in applied health research: a scoping review - Andria Hanbury; Emily Parker; Rebecca Lawton; Jayne Marran; Jane Schofield; Laurie Cave; Lynn McVey; Emma Eyers; Peter Van der Graaf; Roman Kislov (Health Research Policy and Systems)
Abstract Background Initiatives are increasingly encouraging health and social care staff involvement in research, with evidence for patient and organisational level benefits. There is less evidence of the benefits for staff and whether this varies by type of involvement. This scoping review aimed to identify the different ways staff are involved in applied health research, the benefits experienced, and whether this varies by type of involvement. This will help to inform leaders in service organisations, funders, and researchers about how to maximise such benefits. Methods The scoping review followed the JBI methodology. Four databases were searched: CINAHL, MEDLINE, PsycINFO and Scopus. Grey literature was identified via Google, Google Scholar and relevant websites. Records had to be UK-based, published in English between 2003 and 2023 and cover applied health and care research, health care staff involvement and report on benefits. Text was extracted from records, coded afterwards, and quality checked. The benefits were distilled by four research active health care staff. Descriptive statistics and narrative synthesis were used to report the results. Findings In total, 49 records were reviewed, 42 records were from the database search and 7 from the grey literature search. Records were most commonly journal articles (n = 44), covering multiple care settings (n = 15) and mixed professional groups (n = 24), used qualitative methods (n = 22) and focussed on clinical academic roles (n = 21). Six benefits of involvement in research were distilled: personal fulfilment, general competencies/skills, connections/networks, opportunities for learning, opportunities for leading improvements in practice, and using evidence more effectively. Records that focussed on the more intensive clinical academic roles reported more examples of opportunities for leading improvements in practice, and the building of connections and social support. Non-clinical academic records more frequently reported that involvement in research provided opportunities for learning. Conclusions These findings support efforts to involve staff in research, with a range of benefits associated with enhanced job satisfaction, even when research involvement is in a less intense form, such as participation in a study. These findings can be used to encourage involvement, with recommendations for future research to review the benefits for social care staff, and to examine more directly the effect on staff wellbeing and retention.